Trends in Hospitalization for Pediatric Pulmonary Hypertension - Bryan G. Maxwell; Melanie Nies; Chinwe C. Ajuba-Iwuji; John D. Coulson; Lewis H. Romer (2015)
Pulmonary hypertension (PH) has been associated with substantial morbidity and mortality in children, but existing analyses of inpatient care are limited to small single-institution series or focused registries representative of selected patient subgroups. We examined US national data on pediatric PH hospitalizations to determine trends in volume, demographics, procedures performed during admission, and resource utilization.Retrospective cohort study using a national administrative database of pediatric hospital discharges: the Kids' Inpatient Database.Children with PH accounted for 0.13% of the 43 million pediatric hospitalizations in the United States between 1997 and 2012, and discharges demonstrated an increasing trend over the study period (P < .0001). Cumulative, inflation-adjusted national hospital charges for PH hospitalizations rose (P = .0003) from $926 million in 1997 to $3.12 billion in 2012. Patients with PH without associated congenital heart disease (CHD) comprised an increasing and majority (56.4%) proportion over the study period (P < .0001), children without associated CHD admitted at urban teaching hospitals comprised the fastest-growing subgroup. In-hospital, all-cause mortality was high (5.9%) in children with PH, but demonstrated a decreasing trend (P < .0001).Morbidity and mortality of pediatric PH continue to represent substantial and growing health care burdens. Shifts in case mix toward PH not associated with CHD, toward noncardiac procedures, and toward care in urban teaching hospitals will increase pressure to manage resource utilization in this small but growing patient group and to improve expertise and define excellence in PH care across a wide range of clinical settings.